Socio-Cultural Barriers to Reproductive Health and Their Impact on Mental Health: A Case of Young Married Women - Thapaliya, Samjhana; Pant, Chitra Kumar (Chaturbhujeshwar Academic Journal, 2025)
This qualitative study investigates the mental health impact of sociocultural barriers to reproductive health among young married women of the Madhesh community in Harion, Sarlahi, Nepal. Reproductive health, a fundamental human right essential for social, emotional, and physical well-being, is constrained by entrenched patriarchal norms, gender discrimination, and cultural traditions in this community. Through in-depth interviews with three purposively selected married women under 24 years, the study identifies four key themes: gender and social inequality manifested in son preference, dowry, educational discrimination, and enforced silence; marriage-related factors including child marriage, early pregnancy, unpaid labor, and reproductive pressure; nutrition and health access influenced by food hierarchies, poverty, and limited healthcare use; and challenges in natal and postnatal stages characterized by neglect, overwork, malnutrition, and postnatal depression. These issues cause anxiety and low self-esteem, showing that reproductive and mental health are shaped by social and cultural, not just medical, factors. The study calls for integrated health policies and programs addressing gender inequity to improve women’s autonomy and well-being.